Women's Joint Congressional Committee records - Women's Joint Congressional Committee
Correspondence, minutes, reports, information forms, membership lists, financial records, printed matter, and other papers relating to the Committee's work in monitoring and promoting legislation in the areas of education, social welfare, and women's rights. Subjects include civil rights, social security, women's and children's bureaus, maternity and infancy, a department of education, school lunch programs, anti-lynching legislation, and home rule for the District of Columbia. Member organizations represented include the National Consumers' League, National Education Association of the United States, and National Council of Jewish Women. Correspondents include Katharine M. Ansley, Helen W. Atwater, Mary T. Bannerman, Bessie S. Cone, Elizabeth Eastman, Eleanor M. Hadley, Florence Kelley, Margaret C. Maule, Claire Sifton, Florence V. Watkins, and Lenna Lowe Yost.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Committee organized in 1920, shortly after the passage of the Nineteenth Amendment, as a clearinghouse and information center for legislation pending in Congress. Special interests included legislation in the fields of social welfare, education, and women's right. Composed of representatives from national organizations including the National Consumers' League, National Education Association of the United States, and National Council of Jewish Women.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ansley, Katharine M. -- Correspondence; Atwater, Helen W. -- Correspondence; Bannerman, Mary T. -- Correspondence; Cone, Bessie S. -- Correspondence; Hadley, Eleanor M. -- Correspondence; Kelley, Florence, -- 1859-1932 -- Correspondence; Maule, Margaret C. -- Correspondence; Sifton, Claire, -- 1897-1980 -- Correspondence; Watkins, Florence V. -- Correspondence; Yost, Lenna Lowe, -- 1878-1972 -- Correspondence; United States. -- Congress; National Consumers' League; National Council of Jewish Women; National Education Association of the United States; Children -- Societies and clubs; Civil rights; Education and state -- United States; Educational law and legislation; Infants; Lynching; Motherhood; National school lunch program; Social legislation; Social security; Social service; Suffrage -- Washington (D.C.); Women -- Societies and clubs; Women's rights; Washington (D.C.) -- Politics and government